2014
DOI: 10.1016/j.ijnurstu.2013.09.011
|View full text |Cite
|
Sign up to set email alerts
|

The impact of patients’ gender, race, and age on health care professionals’ pain management decisions: An online survey using virtual human technology

Abstract: Background Previous literature indicates that biases exist in pain ratings. Healthcare professionals have been found to use patient demographic cues such as sex, race, and age when making decisions about pain treatment. However, there has been little research comparing healthcare professionals’ (i.e., physicians and nurses) pain decision policies based on patient demographic cues. Methods The current study used virtual human technology to examine the impact of patients’ sex, race, and age on healthcare profe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(47 citation statements)
references
References 15 publications
6
38
0
1
Order By: Relevance
“…30,32,35,37,78 Also similar to previous research is our finding that women's pain, across all weight categories, was more attributed to psychological factors than was men's. 32,35,66 In line with recent conceptualizations, (mis)attribution of pain as psychological in nature could be considered a form of discounting.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…30,32,35,37,78 Also similar to previous research is our finding that women's pain, across all weight categories, was more attributed to psychological factors than was men's. 32,35,66 In line with recent conceptualizations, (mis)attribution of pain as psychological in nature could be considered a form of discounting.…”
Section: Discussionsupporting
confidence: 88%
“…35,37 Similarly in experimental studies, women's pain is judged to be less intense, treated less aggressively, and prescribed psychological treatment more often compared to equivalent men. 30,32,33,78 These systematic gender differences in pain appraisals and pain care decisions are inconsistent with treatment guidelines and are likely to adversely affect patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has implications for maintaining a positive working environment and providing the best possible care by making use of the knowledge and skills of all members of the veterinary team. In human healthcare, similar findings relating to nurses being more prone to rate pain higher, or more willing to administer pain relief are seen, 41,42 This study also demonstrated the relevance of interprofessional working, especially communication, for quality of care and patient safety via the identification of errors. Errors relating to challenges of the system, rather than an individual's mistake, are increasingly recognised in healthcare 43 and are beginning to be researched in the veterinary field, 44 as explored in a further publication from this overarching study.…”
Section: Discussionsupporting
confidence: 63%
“…Disparity greater for nurses than physicians. 31 Despite ACC/AHA PAD guidelines, at discharge, women are significantly less likely than men to be prescribed 3 recommended therapies: statins, aspirin, and β-blockers.…”
mentioning
confidence: 99%